2008
DOI: 10.1063/1.2970163
|View full text |Cite
|
Sign up to set email alerts
|

Structural, electrical, and optical properties of thermally evaporated nanocrystalline PbTe films

Abstract: Nanocrystalline PbTe films are deposited on different substrates at room temperature through thermal evaporation. The films are stoichiometric single-phase polycrystalline with ͑200͒ texture. Electrical properties of the films are analyzed in the framework of a grain boundary channel conduction model. The index of refraction and extinction coefficient of PbTe films are extracted from infrared spectroscopic ellipsometry measurement in the wavelength range of 2-8 m, yielding an optical band gap of 0.386 eV and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
42
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 21 publications
5
42
0
Order By: Relevance
“…They can be deposited on Si in a non-epitaxial manner via thermal evaporation or solution processing [186][187][188]. They also epitomize a class of semiconductors whose polycrystalline form rivals or even outperforms their single crystalline counterparts for IR detection, a unique feature owing to spatial separation of charge carriers near grain boundaries and hence long photo-carrier lifetime [189,190]. As an example, Figure 13 illustrates a PbTe detector integrated with a Ge 23 Sb 7 S 70 ChG waveguide [179].…”
Section: Inmentioning
confidence: 99%
“…They can be deposited on Si in a non-epitaxial manner via thermal evaporation or solution processing [186][187][188]. They also epitomize a class of semiconductors whose polycrystalline form rivals or even outperforms their single crystalline counterparts for IR detection, a unique feature owing to spatial separation of charge carriers near grain boundaries and hence long photo-carrier lifetime [189,190]. As an example, Figure 13 illustrates a PbTe detector integrated with a Ge 23 Sb 7 S 70 ChG waveguide [179].…”
Section: Inmentioning
confidence: 99%
“…At lower temperature range (303 -483) K; the conduction mechanism is due to carrier excited into localized states at the edge of the band. 2 ) at (T a =323 and 373K) for PbTe. It is found that the activation energy tends to increase with the increasing of the annealing temperature.…”
Section: Electrical Properties Of Pbte Films 311dc Conductivity Ofmentioning
confidence: 99%
“…Single crystal PbTe and Pb 1−x Sn x Te have been studied for the fabrication of IR photodetectors and long wavelength laser devices. Boberl et al reported epitaxial PbTe detectors integrated with mid-IR filters and showed enhanced photoresponsivity at room temperature [2]. The narrow band gap IV-VI semiconductors (PbTe) have long been used for mid-infrared optoelectronic device applications [1].…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] In addition, our prior work shows that fast oxygen diffusion along the grain boundaries enhances the optical response of the PbTe material by creating spatial charge separation and thereby increasing the carrier lifetime. 14,15 In this paper, we demonstrate a waveguideintegrated PbTe detector monolithically integrated on a silicon substrate and operating at room temperature.…”
mentioning
confidence: 99%
“…All the thin films for device fabrication (PbTe, Sn, and Ge 23 Sb 7 S 70 glass) are deposited by thermal evaporation used in previously reported protocols. 15,16 A PbTe layer is deposited first, followed by a 300 nm thick Sn contact layer with the Ge 23 Sb 7 S 70 (GeSbS) waveguide layer on top. We choose Ge 23 Sb 7 S 70 chalcogenide glass as the waveguide material given its superior chemical stability and compatibility with PbTe materials.…”
mentioning
confidence: 99%